Activity Patterns among Young Women: A Time Budget Perspective - Renata Winkler; Marta Moczulska (Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie)
Objective: In this article, our aim is to identify and assess changes in the behaviour of young women taking into account the changes regarding gender and cultural roles.